Edge of eternity - Follett, Ken (New York : Dutton, 2014)
East German teacher Rebecca Hoffman discovers she's been spied on by the Stasi for years and commits an impulsive act that will affect her family for the rest of their lives. George Jakes, the child of a mixed-race couple, bypasses a corporate law career to join Robert F. Kennedy's Justice Department, and finds himself in the middle not only of the seminal events of the civil rights battle, but a much more personal battle of his own. Cameron Dewar, the grandson of a senator, jumps at the chance to do some official and unofficial espionage for a cause he believes in, only to discover that the world is a much more dangerous place than he'd imagined. Dimka Dvorkin, a young aide to Nikita Khrushchev, becomes a prime agent both for good and for ill as the United States and the Soviet Union race to the brink of nuclear war, while his twin sister, Tania, carves out a role that will take her from Moscow to Cuba to Prague to Warsaw and into history.
Map on lining papers.
Keywords: World politics -- 1945-1989 -- Fiction; Political fiction; Spy stories